Comparison of the Management Characteristics of Sero-positive and Negative Chickens Against Avian Pneumovirus in Uruguay - Trenchi, G.; Suzuki, K.; Petruccelli, M.; Giossa, G.; Rodriguez, G.; Trenchi, H. (International Journal of Poultry Science, 2010)
The objective of this study was to investigate the risk factors, especially for management characteristics associated with the seropositivity of avian pneumovirus in broiler chickens Uruguay. Seventeen farms of broiler chickens (35 days of age) were studied from October 2008 to April 2009, comprised data collection through questionnaire interviews for each study farm, in combination with blood sample collections for each chicken (n = 1861). Sera were analyzed using a commercial enzyme-linked immunosorbent assay. Univariate and multivariate analyses were used to describe the differences between the two chicken groups categorized according to seropositivity. Percentages of test positive were highly variable between the study farms (0-81%) on the basis of different sample sizes (30-224). The final multivariate logistic regression model indicated that five different study farms were less likely to have seropositive-chickens against avian pneumovirus compared with the reference farm (81% of test positive). Chickens introduced from the two unique hatcheries were less likely to be seropositive in comparison with chickens with no hatchery information.